Intestinal parasites in various animals at a zoo in Malaysia - Lim, Y.A.L.; Ngui, R.; Shukri, J.; Rohela, M.; Naim, H.R.M. (2008)
A survey was undertaken to investigate the prevalence of intestinal parasites from different groups of mammals housed in a zoological garden in Malaysia. A total of 197 faecal samples were collected randomly from various primates (99), hoofed mammals (70) and feline (28). It was discovered that 89.3 of feline, 54.5 of primates and 45.7 of hoofed mammals were infected with intestinal parasites. Intestinal parasites found in primates were Balantidium coli (19.2), Cryptosporidium spp. (14.1), hookworm (10.1), Trichuris spp. (5.1), Ascaris (4.0) and Blastocystis spp. (2.0). For hoofed mammals, hookworm had the highest prevalence (34.3) followed by Trichuris spp. and Cryptosporidium spp. (5.7). Meanwhile, for feline, Toxocara cati was the most prevalent (64.3), followed by Cryptosporidium spp. (14.3), Spirometra spp. (7.1), and hookworm (3.6). Animals that were infected were all asymptomatic with low parasite load. Routine monitoring of the presence of parasites in animals kept in the zoo is imperative in assisting zoo management in the formulation and implementation of preventive and control measures against the spread of infectious parasitic diseases among animals within the zoo or to humans. (C) 2008 Elsevier B.V. All rights reserved.